Eight-and-a-half syndrome: video evidence and updated literature review - Cárdenas Rodríguez, Marco Antonio; Castillo Torres, Sergio Andrés; Chávez Luévanos, Beatriz Eugenia; De León Flores, Laura (BMJ Publishing Group, 2020)
The eight-and-a-half syndrome (EHS)—defined by the combination of a seventh cranial nerve palsy and an ipsilateral one-and-a-half syndrome—is a rare brainstem syndrome, which localises to the caudal tegmental region of the pons. We present a case of the EHS secondary to an inflammatory lesion on a previously healthy 26-year-old woman, with a literature review emphasising the relevance of aetiological assessment.